1990
DOI: 10.1002/pssa.2211170124
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Image Reconstruction with Application in Positron Annihilation

Abstract: Some remarks are made on Cormack's method and on the possibility of its application to two‐dimensional angular correlation of positron annihilation radiation data. The fulfilment of the consistency condition is studied on the example of the experimental data. It is shown that this condition, imposed on the experimental data, improves them making additional advantage of Cormack's method. Some remarks concerning a way of practical using this method are given. Test reconstructions for two anisotropic models and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…24,25 For each Compton profile, ϳ600 000 counts in the peak data channel were accumulated, and each Compton profile was corrected for possible multiple-scattering contributions. A twodimensional momentum density, representing a projection down the c axis of the full three-dimensional density, was reconstructed from each set of five profiles using tomographic techniques 26 and then folded back into the first BZ using the Lock-Crisp-West procedure 27,28 to obtain the occupation density from which the occupied parts of the BZ could be inferred. The occupation density is shown for each composition in Fig.…”
mentioning
confidence: 99%
“…24,25 For each Compton profile, ϳ600 000 counts in the peak data channel were accumulated, and each Compton profile was corrected for possible multiple-scattering contributions. A twodimensional momentum density, representing a projection down the c axis of the full three-dimensional density, was reconstructed from each set of five profiles using tomographic techniques 26 and then folded back into the first BZ using the Lock-Crisp-West procedure 27,28 to obtain the occupation density from which the occupied parts of the BZ could be inferred. The occupation density is shown for each composition in Fig.…”
mentioning
confidence: 99%
“…It was generally supposed that Fourier transform methods need a knowledge of many projections [44][45][46][47][48][49], whereas, as shown in the paper [12], the CM allows to reconstruct ρ(p) basing on a small number of measured spectra. It was explained in the paper [50] where we showed that the necessity of integration with a small ∆ϕ (Eq.…”
Section: Fourier Transform (Ft) Methodsmentioning
confidence: 99%
“…Cormack's method (CM), adopted for symmetry systems [12], has been applied many times for reconstructing electron-positron momentum densities from 2D ACAR data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] as well as for reconstructing line dimensions of the Fermi surface from Compton scattering profiles (i.e. conversion: from 1D to 2D) [29][30][31][32].…”
Section: Gegenbauer and Jacobi Polynomialsmentioning
confidence: 99%
“…Socalled "consistency condition" for 2D data was discussed in Ref. [11] where it was shown that this condition suppresses the noise in the data.…”
Section: Methods Of Extracting Electron-positron Enhancement Facors mentioning
confidence: 99%